Caesarean section by country of birth in New South Wales, Australia. Issue 1 (February 2020) - Trinh, Lieu Thi Thuy; Assareh, Hassan; Achat, Helen; Chua, Seng; Guevarra, Veth
Abstract: Objective: To determine rates of caesarean section by country of birth and by obstetric risks. Methods: We analysed the New South Wales Perinatal Data Collection data of women giving birth between January 2013 and December 2015. Obstetric risk was classified using the Robson's 10-group classification. Multilevel logistic regression with a random intercept was used to measure the variation in caesarean section rate between immigrants from different countries and between regional immigrant groups. Results: We analysed data from 283, 256 women, of whom 90, 750 had a caesarean section (32.0%). A total of 100, 120 women were born overseas (35.3%), and 33, 028 (33.0%) had a caesarean section. The caesarean section rate among women from South and Central Asia ranged from 32.6% for women from Pakistan to 47.3% for women from Bangladesh. For South East Asia, women from Cambodia had the lowest caesarean section rate (19.5%) and women from Indonesia had the highest rate (37.3%). The caesarean section rate for North Africa and the Middle East ranged from 28.0% for women from Syria to 50.1% for women from Iran. Robson groups that accounted for most of the caesarean sections were women who had previous caesarean section (36.5%); nulliparous women, induced or caesarean section before labour (26.2%); and nulliparous women, spontaneous labour (8.9%). Conclusions: The caesarean section rate varied significantly between women from different countries of birth within the same region. Women from some countries of birth had the higher caesarean section rates in some Robson groups.